Beasts and beauties : animals, gender and domestication in the Italian renaissance - Schiesari, Juliana (Toronto Italian studies., 2010)
Beasts and Beauties examines the relationship between domesticity and power by focusing on the contemporaneous development of the invention of the 'pet' and the delineation of the home as a uniquely private enclosure, where the pater familias ruled over his own secluded world of domesticated wife, children, servants, and animals.